2015
DOI: 10.1186/s12864-015-1698-7
|View full text |Cite
|
Sign up to set email alerts
|

Identifying new sex-linked genes through BAC sequencing in the dioecious plant Silene latifolia

Abstract: BackgroundSilene latifolia represents one of the best-studied plant sex chromosome systems. A new approach using RNA-seq data has recently identified hundreds of new sex-linked genes in this species. However, this approach is expected to miss genes that are either not expressed or are expressed at low levels in the tissue(s) used for RNA-seq. Therefore other independent approaches are needed to discover such sex-linked genes.ResultsHere we used 10 well-characterized S. latifolia sex-linked genes and their homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
3
19
0
Order By: Relevance
“…annua, pseudogenisation of its Y alleles (approximately 36%) was similar to that found in other species, such as R. hastatulus (28%, Hough, et al 2014) and S. latifilia (14.5%-30%, Bergero, Qiu, et al 2015;Blavet, et al 2015). This pattern points to an earlier disruption of gene expression of Y-linked genes compared to their pseudogenisation, as found in both S.…”
Section: Limited Gene Loss and Pseudogenation Of Y-linked Genes In Msupporting
confidence: 82%
See 1 more Smart Citation
“…annua, pseudogenisation of its Y alleles (approximately 36%) was similar to that found in other species, such as R. hastatulus (28%, Hough, et al 2014) and S. latifilia (14.5%-30%, Bergero, Qiu, et al 2015;Blavet, et al 2015). This pattern points to an earlier disruption of gene expression of Y-linked genes compared to their pseudogenisation, as found in both S.…”
Section: Limited Gene Loss and Pseudogenation Of Y-linked Genes In Msupporting
confidence: 82%
“…For instance, recent RNAseq studies have found that up to 28% and 14.5% of genes on the Y-chromosome have probably been lost in Rumex hastatulus (Hough, et al 2014) and S. latifilia (Bergero and Charlesworth 2011;Chibalina and Filatov 2011;Bergero, Qiu, et al 2015), respectively. Studies of S. latifolia using BACs suggest a rate of Y-linked gene loss of 30% (Blavet, et al 2015), and analysis based on a partially sequenced genome points to the loss of expression of as many as 45% of Y-linked genes and pseudogenisation through premature stop codons of 23% (Papadopulos, et al 2015).…”
Section: Limited Gene Loss and Pseudogenation Of Y-linked Genes In Mmentioning
confidence: 99%
“…However, deletion sizes in A. thaliana chromosomes are restricted by the presence of essential genes at a high density, including genes necessary for pollen functioning (large deletions cannot be transmitted to the progeny generation 62 ), and possibly genes where two copies are required for zygote viability. In contrast, non-recombining regions such as the S. latifolia Y chromosome are predicted to accumulate repetitive sequences 63 and the Y is indeed much larger than the X chromosome 64 , and there is also direct evidence for the presence of repetitive sequences 65 66 67 . It may thus have a low density of essential genes, and there is evidence for loss of some genes 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The gene density in S. vulgaris has been estimated from sequenced BAC clones to be about 74 genes/Mb (Blavet et al . ), and, assuming a low recombination rate of one cM per Mb, this would imply that the added regions could include at least a 1000 genes.…”
Section: Discussionmentioning
confidence: 99%